Clinical and Psychosocial Predictors of Community Reintegration of Stroke Survivors Three Months Post In-Hospital Discharge (2017)
BACKGROUND: There appears to be a dearth of published literature on the biopsychosocial predictors of community reintegration (CR) among stroke survivors. This study aims to investigate the clinical and psychosocial predictors of CR among stroke survivors three months post in-hospital discharge. METHODS: Fifty-two stroke survivors took part in this prospective exploratory study. The participants’ clinical attributes of motor function (MF), balance (Bal) and psychosocial characteristics of Fall Self- Efficacy (FSE), Balance Self-Efficacy (BSE), Self Esteem (SEst) and Social Support (SS) were assessed pre-discharge and at three months post-discharge. CR was also assessed at three months post-discharge. Data were analyzed using paired t-test, Pearson’s Moment correlation and multiple regressions. Level of significance was set at p = 0.05 RESULTS: The mean age of the participants was 61.21±11.25 years with mean hospital length of stay of 5.31±3.71weeks. There were significant differences in the mean MF, Bal, FSE, BSE, SEst and SS scores of the participants pre- and post-discharge (p < 0.05). Also, there was a significant correlation between CR and each of MF, Bal, FSE, BSE, SEst and SS. Pre-discharge Age (β = 0.226, p = 0.001) and FSE (β = 1.387, p = 0.040) significantly predicted CR. Post-discharge age (β = -0.164, p = 0.005) and Bal (β = 0.142, p = 0.048). FSE (β = 1.243, p = 0.034) also significantly predicted CR. CONCLUSION: Age, Bal and FSE are important predictors of CR among stroke survivors. Therefore, rehabilitation programmes should focus on improving Bal and FSE in order to enhance community reintegration among stroke survivors.